2020
DOI: 10.1007/s40415-020-00599-3
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast genome sequence of Dipteryx alata Vog. (Fabaceae: Papilionoideae): genomic features and comparative analysis with other legume genomes

Abstract: Dipteryx alata Vog. (Fabaceae) is a species of tree native to the Brazilian Cerrado that has economic potential due to its use for food, forage, medicinal, recovery of degraded areas, landscaping and wood extraction. The objective of the present study was to sequence, assemble and annotate the chloroplast genome sequence (cp genome) of D. alata and perform comparative analysis with the cp genome of other species of Fabaceae. The chloroplast is 158,647 bp in length and exhibits a quadripartite structure, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Currently, studies of discovery and characterization of microsatellite markers and studies of population genetics are found in the literature for D. alata (Soares et al, 2012(Soares et al, , 2015Collevatti et al, 2013;Guimarães et al, 2017Guimarães et al, , 2019b. Genomic studies for D. alata include the assembly and characterization of the chloroplast genome (Antunes et al, 2020b). Despite advances in sequencing technology, smaller genomes have been prioritized due to lower costs for obtaining the total sequences set, which in plant includes sequences from the nuclear and organellar genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, studies of discovery and characterization of microsatellite markers and studies of population genetics are found in the literature for D. alata (Soares et al, 2012(Soares et al, , 2015Collevatti et al, 2013;Guimarães et al, 2017Guimarães et al, , 2019b. Genomic studies for D. alata include the assembly and characterization of the chloroplast genome (Antunes et al, 2020b). Despite advances in sequencing technology, smaller genomes have been prioritized due to lower costs for obtaining the total sequences set, which in plant includes sequences from the nuclear and organellar genomes.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study [1], 4 rRNA, 30 tRNA and 76 protein-coding genes (Table 1) have been annotated in the Onobrychis gaubae cpDNA (GenBank: LC647182) with a length of 122,688 bp and also in the O. viciifolia (GenBank: MW007721) with a length of 121,932 bp. 4 rRNA, 30 tRNA and 90 protein-coding genes have been annotated in the cpDNA of O. sativa ssp.…”
Section: Genome Sequencing Assembly and Annotationmentioning
confidence: 99%
“…Chloroplast genomes (plastomes), also called chloroplast DNAs (cpDNAs) contain valuable markers for studying evolutionary relationships and population genetics of plants [1]. In contrast to mitochondrial and nuclear genomes, cpDNAs across spermatophytes (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations